The Dominance of Power Over the Figure of Donald Trump in the Official Presidential Speech of the United States of America (The United States Recognizes Jerusalem as The Capital Of Israel): A Discourse Analysis - Ayu Tiara Maretha (Communicare : Journal of Communication Studies, 2018)
The act to boost nation building is not separated from the role of a political actor who represents a country. Donald Trump’s decision to finally recognize Jerusalem as the capital of Israel is very contrary to US foreign policy over the past 7 decades, which makes it controversial. This raises questions about the dominance of power over a figure of the President of United States in representing his role as a political actor. This research aims to analyze the dominance of power over a figure of Donald Trump as The President of United States through his official presidential speech on recognizing Jerusalem as the capital of Israel. Using a discourse analysis by Teun A. Van Dijk, this research is done by analyzing structures of language based on the full transcript of the video, as The basic assumption of the study of critical discourse is that the language used for various functions has various consequences, whether it is governing, influencing, deciphering, filing, manipulating moving groups or persuading. It can also be implied that certain statement of a powerful political leader can be used to support nation building, in this case is the United States as a superpower.